Mulheres negras e seus cabelos: um estudo sobre questões estéticas e identitárias - Rosa, Camila Simões (Universidade Federal de São Carlos, 2014)
The identity construction process in black women, starting from the relation that they have with their hair , it is the proposal of this study and based on discrimination regarding gender issue, and mainly ethnic-racial, that when are analyzed as social construction induce loss and conflicts in the identity of black women. Through this it is possible find out that the social representation made to the hair of white people as being good and black people as being bad it is part of a racist process and this characteristics fall on the individual. There is a stress zone between white esthetic and black esthetic and the white esthetic is taken as standard of beauty to be sought and followed by black or not black women. From this foundation the goal set for the investigation was: to understand black women and their esthetic analyzing how the hair interfere/interfered in their identity construction along of path life. Based om general goal were definite as specific goals: to understand how the black women mean their identity, identify and analyze racism situation experienced for this women, analyze how the esthetic issue, especially curly hair, is understanding by women related with to be black The study seek to answer the research question: How does the hair define the construction of the identity on the black women path life? As methodology instruments were used the observation with diary fields records, interviews and conversation and participated as cooperators five black women. The collected data were organized analysis screen and from them emerged three analysis focus. The first focus is Experienced of Childhood The black girl in the family and school context provided us an opportunity to understand childhood experienced and the school admission of the women cooperators. It was possible to realize the important of mother figure on the hair treat and we recognize the school as the first space of denial and "inferiorization" of black people body and curly hair. On the second focus, The mean of to be black and the representation of themselves. We concentrated on the cooperators women understanding in the blackness aspects, your experienced related with racism discriminatory practices, the high sexuality about the black woman body, beyond the strategies that they use to overcome the difficulties of being black in the male chauvinist and racist society. Lastly, in the third analysis focus Curly Hair and Black identity we searched to understand the perceptions of cooperator women about identity issues connecting this issues with the relation that they establish with their hair. The results of this investigation showed elements for the racism understanding and allowed us to extend our vision about the preconception experienced daily by black women, We found out that beyond the conflict that they face because of the denial of your esthetics, these women learn ans use strategies to overcome the racism jokes, the myth of racial democracy, the high sexuality of their bodies and the negative stereotypes regarding the blackness. Third study did not have purpose to expose absolute and unquestionable truths, against it, we want to bring some significant contributions to the discussion in the education sector with the purpose to overcome ethnic-racial inequalities.
Keywords: Mulheres; Negras; Estética; Identidade; Black woman; Esthetics issues; Identity; CIENCIAS HUMANAS::EDUCACAO